ANALISIS POLA RENCANA ANGGARAN BIAYA (RAB) PADA PROYEK PEMBANGUNAN PERGUDANGAN BERDASARKAN HSPK KOTA MOJOKERTO - ANDRE RIANTAMA; koespiadi koespiadi (Program Studi Teknik Sipil Universitas Narotama, 2018)
The develop industrial sector, the government and private companies don’t stop to build fulfillment facilities and infrastructure for the people’s lives, among these facilities is the warehouse building, which is the one of the needed society as a job, The role of experienced construction experts is needed to support the development process, especially against the Bill of Quantity. Bill of Quantity put the standard cost of basic unit activity (HSPK) in Mojokerto city for five (5) years back from 2013 to 2017, the intention is for comparison to predict changes in the coming year. The purpose of this paper to produce a pattern of alteration stell building prices based on HSPK Mojokerto city, and get what the factors are the most dominant cause changes in the price of the building. This research method using linear regression analysis were prepared from the Bill of Quantity on warehouse building, according to HSPK of Mojokerto city from 2013 to 2017. From processing the data that has been collected, it has obtained a regression equation trend of building cost /m2 is Y=1.499.963,89+120.780,56*X. The most dominant factor causing price changes buliding is the Portland Cement (PC), Red brick and Wood 5/7, 4/6 for formwork.